Non-O blood type is the commonest genetic risk factor for VTE: results from a meta-analysis of the literature - Dentali, Francesco; Sironi, Anna Paola; Ageno, Walter; Turato, Sara; Bonfanti, Carlo; Frattini, Francesco; Crestani, Silvia; Franchini, Massimo (Seminars in thrombosis and hemostasis, 2012)
It is well known that the ABO blood group exerts a major influence on hemostasis, as O blood group individuals have lower von Willebrand factor and factor VIII levels than non-O blood group subjects. To evaluate the possible clinical implication of the different ABO blood groups on the risk of developing venous thromboembolism (VTE), we conducted a meta-analysis of the existing literature. After an electronic search strategy using Medline and Embase and a manual review of abstract books of the International Society on Thrombosis and Haemostasis and of reference lists of all retrieved articles, we included in the systematic review 38 studies with 10,305 VTE cases. The prevalence of non-O blood group was significantly higher in VTE patients compared with controls with a resulting pooled odds ratio (OR) of 2.09 (95% confidence interval [CI], 1.83, 2.38; p < 0.00001). Similar findings were obtained when the genotypes A1O/BO/A2B (OR 1.73, 95% CI, 1.47, 2.05; p < 0.00001) and A1B/A1A1/BB (OR 1.87, 95% CI, 1.84, 2.44; p < 0.00001) were analyzed. The maximum VTE risk was observed in non-O-factor V Leiden patients (OR 7.60, 95% CI, 3.21, 17.99), while for G20210A prothrombin mutation it was not possible to perform a pooled analysis due to a paucity of published studies. Finally, the association between non-O blood group and VTE was weaker when provoked VTE cases were considered (OR 1.33, 95% CI, 1.18, 1.50), while it was substantially unchanged when unprovoked VTE cases were analyzed (OR 1.88, 95% CI, 1.42, 2.50). In conclusion, considering its prevalence, non-O blood group is a candidate to be one of the most important genetic risk factors for venous thrombosis.